An allotetraploid Brassica napus early‐flowering mutant has BnaFLC2‐regulated flowering. (12th July 2013) - Huang, Yong; Jiang, Ling; Ruan, Ying; Shen, Wenhui; Liu, Chunlin
Abstract: BACKGROUND: Flowering time is an important agronomic trait, and wide variation in flowering time exists among Brassica napus accessions. GX50 early‐flowering mutant, induced from Brassica napus by Ethyl Methane Sulfonate (EMS), exhibits a remarkable early transition from vegetative to reproductive growth . RESULTS: GX50 plants flowered about 60 days earlier than the control wild‐type plant B. napus XY15 under greenhouse conditions. Cytological examination revealed that the GX50 plants form inflorescences as early as from 5 weeks old, flower primordium from 6 weeks old, and siliques from 10 weeks old, whereas 10‐week‐old XY15 plants are still at vegetative growth stage. To unravel the molecular mechanisms underlying the GX50 flowering phenotype, we analyzed the expression of several key regulatory genes. Expressions of all five BnaFLC s ( BnaFLC1 to BnaFLC5 ), BnaFT and BnaSOC1 were detected. Interestingly, BnaFLC s expression levels were lower in GX50 than those in XY15. Among the five BnaFLCs, only the expression pattern of BnaFLC2 corresponded to the timing of floral organ differentiation in GX50. In agreement with previous knowledge that BnaFLCs repress expression of BnaFT and BnaSOC1, increased levels of BnaFT and BnaSOC1 were observed in GX50 compared with XY15 . CONCLUSION: BnaFLC2, but not the other BnaFLC genes, plays an important role in B. napus GX50 floral transition. © 2013 Society of Chemical Industry